Pembelajaran bahasa Inggris for specific purposes - de Araujo, Aniceto Jordao (LingTera, 2018)
Penelitian ini bertujuan untuk mengungkapkan profil STM Negeri Dili Timor Leste, guru bahasa Inggris, dan pihak-pihak yang terkait dengan pembelajaran bahasa Inggris; dan proses pembelajaran bahasa Inggris for specific purposes. Metode penelitian ini adalah deskriptif kualitatif. Subjek penelitian ini adalah guru-guru bahasa Inggris, siswa/i kelas XI dan XII STM Negeri Dili serta dua orang penanggungjawab kurikulum dari Kementerian Pendidikan Timor Leste. Pengumpulan data melalui wawancara, observasi, dokumentasi, dan angket. Analisis data dengan klasifikasi data, transkripsi, verifikasi, dan kesimpulan. Hasil penelitian menunjukkan bahwa pembelajaran bahasa Inggrisfor specific purposes tidak didukung oleh (1) kemampuan sumber daya manusia dan kreativitas guru; (2) perangkat pembelajaran; (3) pelatihan bagi guru bahasa Inggris yang relevan; (4) peningkatan kesejahteraan dan kinerja; (5) budaya dan lingkungan dalam proses pembelajaran siswa. The learning of English for specific purposes Abstract This study aims to reveal the profiles of STM Negeri Dili, Timor Leste, English teachers, and parties related to the English learning; and the English learning process for Specific Purposes. The study employed the qualitative descriptive method. The research subjects were English teachers, male and female students of Grades XI and XII of STM Negeri Dili, Timor Leste, and two people in charge of curriculum the Ministry of Education of Timor Leste. The data were collected by interview, observation, documentation, and a questionnaire. The data analysis through data classification, transcription, verification and conclusion drawing. The results of the study show that the learning of English for Specific Purposes is not supported by (1) the human resources' competencies, teachers' creativity; (2) learning kits; (3), the training for English teachers is relevant; (4) improvement of welfare and performance; (5) culture and environment in students' learning.